A comparative analysis of the use of back massage and Murattal AI-Qur'an on dysmenorrhea pain and anxiety levels - Mamlukah (International Journal of Research in Medical Sciences, 2024)
Background: Dysmenorrhea pain and anxiety are ordinary women's health concerns that can significantly impact their quality of life. This study compared the effectiveness of two interventions, back massage and Murottal Al-Qur'an (listening to specific Quran verses), in reducing pain and anxiety associated with dysmenorrhea. Methods: A randomized controlled trial was conducted involving 69 women diagnosed with dysmenorrhea. Participants were divided into three groups: a back massage group, a Murottal Al-Qur'an group, and a control group. The back massage and Murottal Al-Qur'an groups received their respective interventions for 30 minutes daily during the first three days of their menstrual period. Validated questionnaires were used to assess pain intensity and anxiety levels before and after the interventions. The questionnaires employed were the Numeric Rating Scale (NRS), a well-validated tool that measures pain intensity on a scale of 0 (no pain) to 10 (worst possible pain), and the Zung Self-Anxiety Scale (SAS), an established instrument that assesses various aspects of anxiety using a 4-point Likert scale. Results: Both the back massage and Murottal Al-Qur'an interventions significantly reduced anxiety levels (p<0.001) compared to the control group. Interestingly, the Murottal Al-Qur'an group showed a more significant reduction in pain (p<0.001) compared to both the back massage group (p=0.012) and the control group (no significant change). Conclusions: This study suggests that both Murottal Al-Qur'an and back massages can be effective in reducing anxiety associated with dysmenorrhea. However, Murottal Al-Qur'an appears to be a more effective intervention for managing pain intensity during menstruation.